Creating Opportunities: Heuristic Reasoning in Proactive Dynamic Capability Deployment - Maghzi, Atefeh; Lin, Nidthida; Pfarrer, Michael D.; Gudergan, Siegfried; Wilden, Ralf (Academy of Management Review, 2024)
Research on dynamic capabilities (DCs) has focused primarily on reactive DC deployment (i.e., opportunity discovery) with less attention being paid to proactive DC deployment (i.e., opportunity creation). Drawing on the opportunity creation perspective in entrepreneurship, we argue that proactive DC deployment is characterized by uncertainty, which makes deductive reasoning less effective and thus requires the use of heuristic reasoning. We also incorporate the evolutionary logic of variation, selection, and retention to theorize about the role of heuristic reasoning in the process of proactive DC deployment. Specifically, we integrate the concept of ecologically rational heuristic reasoning to answer two key questions: First, how does ecologically rational heuristic reasoning facilitate proactive DC deployment when the decision context is uncertain? Second, why is ecologically rational heuristic reasoning effective for proactive DC deployment? In summary, our paper advances the ongoing debate concerning DCs and the way in which heuristic reasoning assists a firm in deploying such capabilities.